Overexpression of Wilms tumor 1 gene as a negative prognostic indicator in acute myeloid leukemia. - Xiaodong Lyu (Public Library of Science (PLoS), 2014)
Chromosomal aberrations are useful in assessing treatment options and clinical outcomes of acute myeloid leukemia (AML) patients. However, 40 ∼ 50% of the AML patients showed no chromosomal abnormalities, i.e., with normal cytogenetics aka the CN-AML patients. Testing of molecular aberrations such as FLT3 or NPM1 can help to define clinical outcomes in the CN-AML patients but with various successes. Goal of this study was to test the possibility of Wilms' tumor 1 (WT1) gene overexpression as an additional molecular biomarker. A total of 103 CN-AML patients, among which 28% had overexpressed WT1, were studied over a period of 38 months. Patient's response to induction chemotherapy as measured by the complete remission (CR) rate, disease-free survival (DFS) and overall survival (OS) were measured. Our data suggested that WT1 overexpression correlated negatively with the CR rate, DFS and OS. Consistent with previous reports, CN-AML patients can be divided into three different risk subgroups based on the status of known molecular abnormalities, i.e., the favorable (NPM1(mt)/no FLT3(ITD)), the unfavorable (FLT3(ITD)) and the intermediate risk subgroups. The WT1 overexpression significantly reduced the CR, DFS and OS in both the favorable and unfavorable groups. As the results, patients with normal WT1 gene expression in the favorable risk group showed the best clinical outcomes and all survived with complete remission and disease-free survival over the 37 month study period; in contrast, patients with WT1 overexpression in the unfavorable risk group displayed the worst clinical outcomes. WT1 overexpression by itself is an independent and negative indicator for predicting CR rate, DFS and OS of the CN-AML patients; moreover, it increases the statistical power of predicting the same clinical outcomes when it is combined with the NPM1(mt) or the FLT3(ITD) genotypes that are the good or poor prognostic markers of CN-AML.